A 10-year critical review on hydrogen peroxide as a disinfectant: could it be an alternative for household water treatment? - Kamila Jessie Sammarro Silva; Lyda Patricia Sabogal-Paz (Water Supply, 2022)
Considering that a large fraction of the global population relies on self-supplied drinking water systems, household water treatment (HWT) technologies may assist achieving the United Nations' Sustainable Development Goal 6.1, which aims at safe drinking water for all by 2030. Hydrogen peroxide disinfection has been widely known as an effective approach for microorganism inactivation, however, it has not been much explored as a standalone solution in sanitation. In this sense, this review presents systematically organized information extracted from papers on H2O2 disinfection from 2011 to 2021. Filtered data was analyzed by content and network visualization, raising a discussion on whether H2O2 could be a potential HWT intervention, and which limitations and prospects are there for its research and implementation. In short, we found a lack of consistency in operational conditions, as most of the retrieved studies address individual use of H2O2 as control to combined treatments. Additionally, oxidant demand and kinetics considering local water quality are lacking, as well as information on residual neutralization, toxicity, and up-scaling. This critical review reveals gaps that encourage further research tackling different disinfection challenges, so that this alternative can be evaluated for implementation as an HWT technology, particularly at context-specific situations. HIGHLIGHTS Though widely applied in decontamination, H2O2 is not popular in water disinfection.; Retrieved records do not include data on H2O2 as an HWT.; Operational conditions found for liquid H2O2 use often favor catalytic treatments.; Context-specific studies are recommended to evaluate HWT feasibility.;